Feasibility study for low-head hydropower on the Mill River, Northampton, Massachusetts (Curran Associates, Inc., Northampton, MA (USA), 1979)
Five existing dams along a 6.5-mile reach of the Mill River in the City of Northampton, Massachusetts were studied to assess the feasibility of developing the sites for low-head hydroelectric power generation. Each of the dams was inspected to evaluate existing conditions and necessary work required to rehabilitate the structures. Analyses of hydrology and power potential were carried out and a packaged tube turbine-generator unit was found to be suitable for installation at all sites. Project layouts were developed making maximum use of existing structures and natural and man-made features. Capital and operation and maintenance costs were estimated based on the project layouts and the selected turbine-generator units. Financial analyses were performed using a set of baseline assumptions. Sensitivity tests of alternative assumptions were also prepared, along with analyses of assistance program alternatives. Finally, the legal, environmental, and socio-institutional considerations affecting development of the hydro projects were identified and reviewed. Hydro developments on the Mill River were found to be technically feasible, presenting no extraordinary engineering, environmental, or legal problems. However, none of these projects, either individually or jointly, would be financially feasible without substantial assistance in the form of capital grants.